English Language Teaching Methods: State of the Art in Grammar Instruction - Rusdiana Junaid (Universitas Cokroaminoto Palopo, 2014)
The teaching of grammar has fluctuated and shifted over years. This paper addresses issues such as different ways of teaching grammar, changes in ideas, and practices at the present stage of its development as well as the current state of the art in grammar instruction. Several grammar textbooks which were published in different years also are looked at in order to discover the extent of change in terms of the materials used to teach grammar from time to time. A considerable array of English language teaching methods is available for teacher to utilize since 1980s. Before deciding to employ a particular method, however, educational practitioners need to take several things into consideration such as the objectives of the instruction, the needs, the interests, the expectation, the age, and the level of the learners, and the available supporting facilities. Equally important, the possible constraints such as the environment where the students are learning, the time, and the expectation of the institution are also needed to be considered.